Effect of integrated nutrition on productivity, profitability and quality of French bean (Phaseolus vulgaris) - KUMAR, RAKESH; DEKA, BIDYUT C; KUMAWAT, NARENDRA; THIRUGNANAVEL, A (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted to investigate the effect of integrated nutrition along with application of micronutrient and biofertilizers on productivity and profitability of french bean (Phaseolus vulgaris L.) at the ICARRC for NEH Region, Nagaland Centre, Jharnapani, during rabi 2013–15. Treatment consisted of four nutrition levels, viz. control, 100% RDF (80-60-30-20 kg NPKS/ha), 100% RDN (RDN:80 kg/ha through 16 t/ha of FYM), 75% RDF + 25% RDN and 100% RDF + 25% RDN in main-plot and five levels of biofertilizers + micronutrient, viz. control, PGPR (Rhizobimum + Bacillus + Pseudomonas), PGPR + 5 kg Zn/ha, PGPR + 1.5 kg Mo/ha and PGPR + 5 kg Zn + 1.5 kg Mo/ha in sub-plot. Experiment was laid out in split-plot design and replicated thrice. Significantly higher seed yield (1630 kg/ha) was recorded with application of 100% RDF + 25% RDN, which was 30% higher over 100% RDN. Maximum net returns (₹ 21399/ha), B:C ratio (1.31), production efficiency (15.8 kg/ha/day) and economic efficiency (₹ 305/ha/day) were noted with 100% RDF + 25% RDN. Maximum grain yield (1551 kg/ha) had recorded with PGPR +5 kg Zn ha+1.5 kg Mo/ha. Maximum net returns (₹ 29941/ha), B:C ratio (1.30), production efficiency (15.1 kg/ ha/day) and economic efficiency (₹ 210/ha/day) were also noted with PGPR+5 kg Zn ha + 1.5 kg Mo/ha. Thus, to achieve the higher productivity and profitability, french bean could be grown with 100% RDF+25% RDN through organic manures (FYM) and seed inoculation with PGPRs + micronutrient in foot hill condition of Eastern Himalayas.